Internal and External Factors that Affect Employee Motivation at Materna Medan Hospital - Joshua Andre Wijaya; Ermi Girsang; Ali Napiah Nasution (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Employees are the main capital in a company or organization including hospitals. Good health services are produced by hospital employees who have great motivation in working. Motivation is influenced by basic human needs including physiological needs, a sense of belonging, a sense of security, self-actualization, and appreciation. This study aims to determine and assess external and internal factors that affect employee motivation at Materna Hospital Medan. This research is quantitative research with a cross-sectional approach. The population of all employees working at Materna Hospital Medan amounted to 137 people and all of them were sampled. Data collection techniques through questionnaire dissemination, documentation, and literature study. The analysis method uses univariate, multivariate, and bivariate analysis using multiple linear regression equations. Research findings show that internal factors in the form of recognition affect employee motivation at Materna Medan Hospital while internal factors in the form of responsibility and work itself do not influence. External factors in the form of compensation, supervisors, and relationships with colleagues affect the motivation of employees at Materna Medan Hospital while external factors in the form of working conditions do not influence. Internal and external factors that predominantly influence motivation are internal factors in the form of recognition. It is recommended to hospital management/leaders give statements of recognition to employees according to their performance, and compensate accordingly and supervisors should understand the nature and characteristics of employees who are subordinates to be able to provide appropriate motivation.Keywords : Internal Factors, External Factors, Work Motivation, Hospital Employees